Structure and function of soil microbial communities in fertile islands in austral drylands - Toledo, Santiago (2022)
Fertile islands are an important determinant of ecosystem functioning in drylands. These resourcerich patches are maintained by complex interactions among biotic and abiotic factors. Soil microorganisms are responsible for essential ecosystem processes and could affect the ability of fertile islands to capture and cycle nutrients, both directly and indirectly enhancing the fertile island effect. In this context, we aimed to evaluate the attributes of soil microbial communities (abundance and activity), elucidate key drivers of the fertile island effect and analyze relationships with a range of soil parameters (physicochemical). The soils under shrub canopies had higher values of microbial biomass carbon (MBC) and soil basal respiration (SBR) rates than soils from intercanopy spaces. However, no differences were observed in Soil Organic Carbon (SOC) or in fungal and bacterial abundances between the microhabitats. Soil nutrient stocks (NPK) and pH values had a positive correlation with MBC and SBR. Also, a positive correlation was observed for fungi abundance and the K content of the soil. We also observed a positive correlation between the bacterial abundance and soil N content. This study suggests that M. tridens can be considered a keystone species that generates fertility islands, critical for biodiversity and ecosystem functioning. The keystone role that M. tridens plays in this system underscores the importance of improving our understanding of these interactions (plant–soil-microorganisms), especially important as drylands expand and aridity increases due to climate change in the second half of this century.